Implementasi Program Literasi terhadap Eskstrakkulikuler di MTsN 2 Medan - Izhra, Farel; Harahap, Nila Riana; Nasution, Sahrina; Devianty, Rina (Ikatan Dai Indonesia, 2023)
This study aims to explain the condition of the extracurricular literacy program at MTSN 2 Medan. In addition, it also explains the effectiveness and constraints that occur in the development of this literacy program at MTSN 2 Medan. This research uses descriptive qualitative research. This study provides an overall picture of the conditions, effectiveness, and obstacles that occur in literacy programs. The results of the research show that the literacy program has not run optimally. Problems with the literacy program in learning Indonesian that occurred at MTSN 2 Medan included irrelevant learning strategies, the availability of inadequate and incomplete facilities and infrastructure, and students' low interest in reading. Sources of data in this study are documents and school implementation processes literacy program. The data in this study were collected using documentation, interviews and observation methods. The results of this study indicate that the governance of extracurricular literacy at MTSN 2 Medan is as follows (1) First, the school planning for the literacy program has been carried out by setting literacy goals for the school movement program. However, this planning has not been based on a needs analysis (2) extracurricular activities about Indonesian that have not been implemented at this school (4) the control that has been carried out is still limited to ensuring that the Thursday reading program is carried out or not. Controls to improve program quality have not been carried out. The management of the school literacy movement program needs to be managed properly, starting from the strategic planning process, organizing by giving job descriptions, implementing programs in accordance with strategic planning, and continuous evaluation